The Role of the Principal as a Leader in Shaping Effective Schools: A Multi-case Study at MAN 1 Tulungagung and SMAN 1 Kedungwaru - Kusmaduni, Fati’ah; Akhyak, Akhyak; Maunah, Binti (Publisher Cv. Inara, 2026)
This study aims to investigate the determinant role of the principal as a leader in reconstructing a quality culture towards an effective school. Employing a qualitative approach with a multi-case study design, the research was conducted at two sites with distinctive characteristics: MAN 1 Tulungagung (based on religious values) and SMAN 1 Kedungwaru (based on professional-secular standards). Data were collected through in-depth interviews, participant observation, and documentation studies, which were then analyzed using the interactive model by Miles, Huberman, and Saldana. The results reveal a substantive finding in the form of a